Racial and Ethnic Disparities in Dietary Intake and Quality Among United States Veterans - Xuan-Mai T Nguyen; Yanping Li; Stacey B Whitbourne; Luc Djousse; Dong D Wang; Kerry Ivey; Walter C Willett; John Michael Gaziano; Kelly Cho; Frank B Hu (Current Developments in Nutrition)
Background: Dietary quality plays an important role in disease development and prognosis, and diet is also a key contributor to disparities in many chronic diseases and health conditions. Objectives: This study aimed to assess racial and ethnic disparities experienced by veterans; we examined food intake and dietary quality across different racial and ethnic groups of United States veterans. Methods: The study included 420,730 males and females aged 19–107 y (91.2% males) enrolled in the Veterans Affairs Million Veteran Program with plausible dietary intake measured by food frequency questionnaire. Dietary quality was evaluated with dietary approaches to stop hypertension (DASH) score. Dietary intakes of various race and ethnicity groups were standardized to the age distribution of non-Hispanic White participants, separately for males and females. Differences across race and ethnicity groups were compared using general linear regression models after adjustment for socioeconomic and lifestyle factors as well as military service. Results: Compared to non-Hispanic White males, non-Hispanic Black males had a relatively lower DASH score, higher red and processed meats, higher sugar-sweetened beverages (SSBs), and lower low-fat dairy intakes. Non-Hispanic Asian males had a relatively higher DASH score as compared to non-Hispanic White males with relatively higher intakes of fruits and vegetables and relatively lower intakes of sodium, red meat and SSBs. Age-standardized DASH scores of Hispanic males and “Other” race/ethnicity groups were not statistically different from non-Hispanic White males. Similar race and ethnicity dietary patterns were found in females, although not all reached a statistically significant level. Conclusions: A modest difference in overall dietary quality (i.e., DASH score) was observed, but unique differences in food preferences across the different racial/ethnic groups were identified. Findings from our study may provide insight for the potential development of specific interventions to help address nutritional disparities experienced among veterans.